(Analysis of Stateless Person and Dual Nationality Children in the Perspective of Indonesian Immigration) - Della Palupi Anggraeni; Tony Mirwanto (Polteknik Imigrasi, 2019)
Citizenship is the right of everyone without exception. With citizenship, a person will get certainty and protection from a country. The nationality of a person has been recognized in international conventions. With the convention, there should be no individual who lives without citizenship status or is commonly referred to as a stateless person. However, even though there has been an international agreement regulating the status of a Stateless Person according to international rules, the existence of a permanent stateless person inhabits the sovereign area of a country. Even the rights they have to become a Stateless Person are often violated by the country where the Stateless Person is located. Apart from stateless persons, another problem regarding citizenship is the existence of dual citizenship or what is called a bipartite. In Indonesia, there is no dual citizenship, but limited dual citizenship. This has been regulated in Law No. 12 of 2006 concerning Citizenship of the Republic of Indonesia. Stateless persons and children with dual nationalities are often problems that need attention.